(untitled) (Veterinária Notícias, 2018)
This work was developed to evaluate the effects of the size and the apical and basal portions of the tiller on the morphology of elephant grass (Pennisetum purpureum cv. Napier). Two experiments were performed. In the first one, the characteristics were evaluated of basal tiller with four sizes (80, 120, 160 and 200 cm). A completely randomized design was used, with three replications. In the second experiment, the morphology of the basal and apical portions, from small tillers (100 cm) and large (180 cm) elephant grass were evaluated. The design was completely randomized and the split-plot scheme was used, with three replications. The numbers of living and dead leaves, stem and leaf lengths, leaf blade width, and tiller mass increased linearly with elephant grass size. The basal portion of the elephant grass tiller had a higher mass (56.2 g), higher percentages of leaf dead (2.1%) and live stem (89.5%), and a lower percentage of live leaf blade (23.4%) than the apical portion. With the increase in size, the elephant grass tiller presents a higher percentage of structural tissues and with a higher stage of development, as well as a lower percentage of photosynthetic tissues. The apical portion of the elephant grass tiller has a higher percentage of photosynthetic tissues and a lower percentage of structural tissues and a higher stage of development compared to the basal portion of the tiller.